(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article discusses the improvement of the methodology for preparing masters of technical specialties for research activities. It emphasizes the need for developing scientific thinking, research competence, and innovation-oriented skills among future engineers. The paper also proposes a model for integrating theoretical knowledge with practical research experiences through modern pedagogical and digital tools.